2018
DOI: 10.1037/dev0000567
|View full text |Cite
|
Sign up to set email alerts
|

From science student to scientist: Predictors and outcomes of heterogeneous science identity trajectories in college.

Abstract: This five-year longitudinal study investigates the development of science identity throughout college from an expectancy-value perspective. Specifically, heterogeneous developmental patterns of science identity across four years of college were examined using growth mixture modeling. Gender, race/ethnicity, and competence beliefs (efficacy for science tasks, perceived competence in science) were modeled as antecedents, and participation in a science career after graduation was modeled as a distal outcome of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
110
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 74 publications
14
110
3
Order By: Relevance
“…For example, although subgroups of students exhibited declines in task value (Archambault et al, 2010; Musu-Gillette et al, 2015) and science identity (Robinson, Perez et al, 2018), the full samples in these studies did not display this pattern of decline. Most relevant to the current study is a longitudinal study examining change in science identity in a sample of elite college students throughout college; results indicated that declines in science identity were relatively rare, suggesting that educators may want to target interventions specifically on students who exhibit declines rather than the whole college population (Robinson, Perez et al, 2018). This prior study also speaks to the dual nature of identity: its relative stability, with very slow change for the majority of students, but with the potential for rapid change during college for some.…”
Section: Development Of Science Identity During Collegementioning
confidence: 63%
See 4 more Smart Citations
“…For example, although subgroups of students exhibited declines in task value (Archambault et al, 2010; Musu-Gillette et al, 2015) and science identity (Robinson, Perez et al, 2018), the full samples in these studies did not display this pattern of decline. Most relevant to the current study is a longitudinal study examining change in science identity in a sample of elite college students throughout college; results indicated that declines in science identity were relatively rare, suggesting that educators may want to target interventions specifically on students who exhibit declines rather than the whole college population (Robinson, Perez et al, 2018). This prior study also speaks to the dual nature of identity: its relative stability, with very slow change for the majority of students, but with the potential for rapid change during college for some.…”
Section: Development Of Science Identity During Collegementioning
confidence: 63%
“…Identity-related attainment value shares characteristics with theoretical conceptualizations of identity in the broader identity literature (e.g., Luyckx, Goossens, Soenens, & Beyers, 2006; Marcia, 1993; Markus & Nurius, 1986; Schwartz, Zamboanga, Luyckx, Meca, & Ritchie, 2013; see Robinson, Perez et al, 2018 for a more detailed discussion), such as the focus on absolute salience or importance to one’s identity. However, in contrast to conceptualizations of identity as a whole, or on identity processes regardless of contents, expectancy-value theory’s focus on the identity contents in the context of a particular task or domain is a defining characteristic of this conceptualization (Eccles, 2009).…”
Section: Theoretical Framework: Identity From An Expectancy-value Permentioning
confidence: 91%
See 3 more Smart Citations